Survei Penerapan Pijat Oksitosin di Unit Pelayanan Keperawatan Maternitas - Ratnawati, Eka; Agustina, Clara (Jurnal Kesehatan, 2023)
Riskesdas data (2018) showed that 3.9% toddlers have malnutrition status and 13.8% with malnutrition due to lack of food intake and infection disease. The coverage of breastfeeding in Indonesia is 9.3% of the target of 80% because of exclusive breastfeeding failure, with one of the factors is the lack of stimulation of the oxytocin and prolactin hormones. Oxytocin massage is effective for stimulating the release of the oxytocin hormone, appropriate to do on day 0-3 puerperium at health service. This study aims to determine the implementation of oxytocin massage performed by midwife and nurse in the obstetric ward. This study used quantitative design with survey method. The questionnaire was presented as a google form to midwives and nurses at YAKKUM’s hospital, Public Health Centre Temanggung, and midwives alumni Semarang. The analysis used distribution frequencies statistics, percentages, and maximum/minimum/average values. 31.6% of 38 midwives/nurses were aged 31-40 years, Diploma 3 Midwifery graduates (50%), has been working for more than 10 years (65.8%), work in hospitals (52.6%), manage 1-3 patient/day (65.8%). Midwives/nurses (52.6%) did not do oxytocin massage because there was over workload and they had not received information/training about oxytocin massage (15,8%). 50% of midwives/nurses did not do the intervention due to lack of information and training, over workload, and do not having enough time properly to do the oxytocin massage. Uncooperative patients and the perception of there is no need to do the oxytocin massage in the community are also other reasons of why this intervention is not optimal. Health workers are expected to be proficient in terms of knowledge, attitudes and skills in performing oxytocin massage for postpartum mothers when the patients are still at the health service (days 0-3), and are also expected to be able to teach it to families in order independently continue it at home.